Multifunctional cantilevers for simultaneous enhancement of contact resonance and harmonic atomic force microscopy. (30th April 2021) - Wang, Wenting; Zhang, Kaidi; Zhang, Wenhao; Hou, Yaoping; Chen, Yuhang
Abstract: To enhance contact resonance atomic force microscopy (CR-AFM) and harmonic AFM imaging simultaneously, we design a multifunctional cantilever. Precise tailoring of the cantilever's dynamic properties is realized by either mass-removing or mass-adding. As prototypes, focused ion beam drilling or depositing is used to fabricate the optimized structures. CR-AFM subsurface imaging on circular cavities covered by a piece of highly oriented pyrolytic graphite validates the improved CR frequency to contact stiffness sensitivity. The detectable subsurface depth and cavity radius increase accordingly by using the multifunctional cantilever. At the same time, the free resonance frequency of the second mode is tuned to an integer multiple of the fundamental one. Harmonic AFM imaging on polystyrene and low-density polystyrene mixture shows the improved harmonic amplitude contrast and signal strength on the two material phases. The multifunctional cantilever can be extended to enhance other similar AFM operation modes and it has potential applications in relevant fields such as mechanical characterization and subsurface imaging.